2016
DOI: 10.3390/vetsci3030017
|View full text |Cite
|
Sign up to set email alerts
|

Cat Mammary Tumors: Genetic Models for the Human Counterpart

Abstract: The records are not clear, but Man has been sheltering the cat inside his home for over 12,000 years. The close proximity of this companion animal, however, goes beyond sharing the same roof; it extends to the great similarity found at the cellular and molecular levels. Researchers have found a striking resemblance between subtypes of feline mammary tumors and their human counterparts that goes from the genes to the pathways involved in cancer initiation and progression. Spontaneous cat mammary pre-invasive in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 147 publications
(225 reference statements)
1
26
0
Order By: Relevance
“…Due to the similarities between human breast cancer and feline mammary carcinoma [ 6 10 ], new clinical studies on FMC may identify novel diagnostic markers and therapeutic targets that can probably be used in human patients. Recently, it was demonstrated that stroma cells of breast tumors synthesize the chemokine SDF-1, which via its cognate receptor (CXCR4) supports tumor growth through autocrine and paracrine mechanisms [ 14 , 19 , 24 , 41 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the similarities between human breast cancer and feline mammary carcinoma [ 6 10 ], new clinical studies on FMC may identify novel diagnostic markers and therapeutic targets that can probably be used in human patients. Recently, it was demonstrated that stroma cells of breast tumors synthesize the chemokine SDF-1, which via its cognate receptor (CXCR4) supports tumor growth through autocrine and paracrine mechanisms [ 14 , 19 , 24 , 41 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…The feline mammary carcinoma (FMC) is very common in cat (12-40% of all neoplasms), showing overexpression of the HER2 protooncogene in 33%-60% of the cases [ 1 5 ]. Sharing phenotypic and genotypic similarities with human breast tumor [ 6 10 ], spontaneous FMCs can also be classified in the same subtypes (luminal A, luminal B, luminal B-like, epidermal growth factor receptor type II-positive and triple negative) [ 7 , 11 ], being considered a suitable model for breast cancer studies.…”
Section: Introductionmentioning
confidence: 99%
“…The HER2-positive subtype is characterized by a HER2 overexpression and a lack of hormone receptors (estrogen receptor (ER) and/or progesterone receptor (PR)), while the triple negative tumors are defined by the absence of ER, PR and HER2 expression, each representing 15–20% of all breast cancer cases [ 1 , 3 ]. As in human breast cancer [ 4 ], FMC presents an aggressive and infiltrative behavior [ 5 , 6 ], with both HER2-positive and triple negative (TN) subtypes showing worse prognosis than luminal A and B subtypes. Furthermore, a surgical approach is often necessary for the treatment of FMC, as the adjuvant chemotherapy (cyclophosphamide, vincristine, doxorubicin) is not useful in some cases [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…The occurrence of spontaneous tumors in certain animals makes them suitable models for the study of tumorigenesis, for improvement of diagnostic tools and for the development of successful therapies in humans. In addition, the shorter lifespan combined with a faster progression of cancer in model species allows for the completion of trials and faster data collection [4]. Experimental animal models of carcinogenesis have been used as models for human breast cancer and Raman spectroscopy has been used to assess the aggressiveness of tumors [5].…”
Section: Introductionmentioning
confidence: 99%